“The Master and Margarita” as a “Strong” Text of Russian Culture: Translation Aspect - Razumovskaya, Veronica (Respectus Philologicus, 2015)
The paper deals with the original inexhaustibility and translation multiplicity as new literary translation categories. Particular attention is paid to the information ambiguity of “strong” literary texts, which directly results in the generation of numerous centres of translation attraction. A “strong” text of Russian culture The Master and Margarita and its secondary texts resulting from the performed interlingual and intersemiotic translations served as the material for the present study. The centre of translation attraction, which is formed from the Bulgakov’s text, is considered from the standpoint of translation theory and literary criticism, which corresponds to the universal scientific principle of complementarity and provides a complementary approach to the “strong” text as a research object. The formation and further functioning of the centres of translation attraction is of particular interest in the case of using a “strong” literary text of Russian culture as an attractor of literary translation due to the traditional literocentrism of the Russian culture. Numerous translations of the novel provides “expendability” of a culturally significant text in the temporal and cultural spaces and serve as a guarantee of its “preservation” and survival.
Keywords: “strong” text; literocentrism; a centre of translation attraction; original inexhaustibility; translation multiplicity